Variables Connecting Parental PTSD to Offspring Successful Aging: Parent–Child Role Reversal, Secondary Traumatization, and Depressive Symptoms - Hoffman, Yaakov; Shrira, Amit (Frontiers in Psychiatry, 2019)
The effects of parental trauma on offspring of Holocaust survivors (OHS) are debated in the literature. Recently, scholars suggested that it may be more productive to ask when and via which mechanisms such effects are observed. Following, the current study examines if parental Holocaust-related posttraumatic stress disorder (PTSD) symptoms are linked with the aging processes of their middle-aged offspring. Beyond this association, we also suggested a putative mediation path, indicating three underlying mechanisms by which parental trauma lingers on: perceived parent–child role reversal, secondary traumatization, and depressive symptoms. Using a convenience sample of 682 community-dwelling participants, comprising 341 older adult parent–middle-aged offspring dyads (M age = 81.71 and 54.58 for parents and offspring, respectively) to address this issue. Parents reported PTSD with the valid measure of PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders, fifth edition. OHS reported perceived parent–child role reversal, secondary traumatization, depressive symptoms, and completed indices of successful aging. Based on parents’ reports, we divided the parent–offspring dyads into three groups: OHS whose parents had probable PTSD (n dyads = 43), OHS whose parents did not have PTSD (n dyads = 161), and comparison with parents who did not undergo the Holocaust (n dyads = 137). Findings reveal that OHS with parents suffering from probable PTSD aged less successfully than comparisons. Serial mediation analyses validated the aforementioned putative pathway (perceived parent–child role reversal, secondary traumatization, and depression) linking parental PTSD with offspring successful aging. Our findings are discussed through a vignette depicting a fictional OHS character. These underlying mechanisms suggest that different types of interventions, each geared towards a specific mechanism, may mitigate the lingering effect of parental PTSD on diminished OHS successful aging.